2008
DOI: 10.1152/ajpheart.00749.2007
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of the mouse α-calcitonin gene-related peptide gene increases the vulnerability of the heart to ischemia-reperfusion injury

Abstract: Huang R, Karve A, Shah I, Bowers MC, DiPette DJ, Supowit SC, Abela GS. Deletion of the mouse ␣-calcitonin gene-related peptide gene increases the vulnerability of the heart to ischemia-reperfusion injury. Am J Physiol Heart Circ Physiol 294: H1291-H1297, 2008. First published January 11, 2008 doi:10.1152/ajpheart.00749.2007.-Calcitonin gene-related peptide (CGRP), a potent vasodilator released from capsaicin-sensitive C-fiber and A␦-fiber sensory nerves, has been suggested to play a beneficial role in myocard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
26
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 38 publications
3
26
0
Order By: Relevance
“…The concomitant hypertrophy in αCGRPKOs and loss of increased GPX-1 gene expression at 28 days is in keeping with studies using GPX-1 KO mice which revealed protection against AngII-induced artery functional and cardiac remodeling changes. 37,39 We provide novel evidence linking αCGRP with vascular protection against enhanced oxidative stress in a model of hypertension, consistent with evidence from cardiac models 8,40 and an atherosclerosis model. 41 We further provide evidence of enhanced ROS generation in αCGRPKO-AngII mice at day 28, as shown recently in a wire-induced vascular injury model.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The concomitant hypertrophy in αCGRPKOs and loss of increased GPX-1 gene expression at 28 days is in keeping with studies using GPX-1 KO mice which revealed protection against AngII-induced artery functional and cardiac remodeling changes. 37,39 We provide novel evidence linking αCGRP with vascular protection against enhanced oxidative stress in a model of hypertension, consistent with evidence from cardiac models 8,40 and an atherosclerosis model. 41 We further provide evidence of enhanced ROS generation in αCGRPKO-AngII mice at day 28, as shown recently in a wire-induced vascular injury model.…”
Section: Discussionsupporting
confidence: 80%
“…CGRP acts via a G-protein-coupled receptor (calcitonin-like receptor) when dimerized with a single transmembrane-spanning receptor activity-modifying protein RAMP1 2 signaling via cAMP and other pathways. 3,4 CGRP does not play a primary role in the regulation of basal blood pressure (BP) in normal individuals 5,6 but is suggested to have protective properties, in cardiovascular disease, 7,8 including attenuation of vascular smooth muscle proliferation, 9 hyperplasia, 10,11 and stimulation of endothelial cell proliferation 12 and endothelial progenitor cells. 13 Evidence indicates the importance of CGRP in aggressive models of rodent hypertension that are centered on the kidney.…”
mentioning
confidence: 99%
“…The increases in the infarct size of myocardium by antagonisms of endogenous CGRP receptor may indicate the cardioprotective property of the afferent nerves are mediated by the neuropeptide, which was supported by previous reports showing the exogenous CGRP protecting myocardium [20], enhancement of myocardial injury after knockout of the gene encoding the synthesis of CGRP [36], reduction of infarct size by lipoxygenase, an agonist of transient receptor potential vanilloid 1 (TRPV1) [2,37] and increase of infarct size [22], mortality rate and tissue apoptosis [38,39] by TRPV1 gene knockout. However there was opposite report showing exogenously administered CGRP caused systemic hypotension and augmented post-ischemic coronary flow, in which no cardioprotective effect of CGRP could be proven [2].…”
Section: Discussionsupporting
confidence: 61%
“…These diseases are associated with the dysregulation of renin-angiotensin-aldosterone system (RAAS). Afferent nerve-derived calcitonin gene-related peptide (CGRP) is identified as a potent vasodilator and a hypotensive peptide [12], which has protective properties in cardiovascular disease [13, 14]. CGRP release is stimulated by mechanisms that include angiotensin II and sympathetic nerve reflexes [12, 15].…”
Section: Introductionmentioning
confidence: 99%